Corn among the popolucas of the Sierra, Veracruz, Mexico. Notes of his story (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
The intention of the article is to show part of the indigenous knowledge, in general, and of the popoluca culture, in particular; referring to the milpa system, exposing notions and productive practices, ceremonial and symbolic associated with the cultivation of corn in localities in the southern region of the state of Veracruz, Mexico; product of fi eldwork carried out between 1993-1995, as part of the Activities of the Project Sierra de Santa Marta A.C. (University of Carleton, Canada-National Autonomous University of Mexico). The methodology used was concretized with the application of in-depth interviews, the observation and transects in corn plots, mainly. The results of the work show the way in which the agricultural work between the popolucas represents a system that is covered with a complex logic through which man interacts,nature and the spiritual; in the process the mythical role of Jomshuk, God of corn, stands out.Ancestral.
Keywords: Corn; Popoluca; Cultivation; Ritual; Jomshuk